BRAND STRENGTH BASED ON REALISTIC AND EMOTIONAL FEATURES AND STRATEGY OF MANAGING IT - Iastremska , Olesia (INNOVATIVE TECHNOLOGIES AND SCIENTIFIC SOLUTIONS FOR INDUSTRIES, 2022)
The article is devoted to the study of the definition of the strength of the brand by its main features: objective, characterizing the realistic benefits of using the brand, such as profit, cost savings, etc., and subjective, which characterizes the emotional satisfaction of the use of products of a particular brand or cooperation with an enterprise, which consists in the attractiveness of the brand. The purpose of the article is to develop proposals from: determining the strength of the brand’s influence by realistic and emotional features, identifying strategies for managing it. The object is the process of brand management of products or enterprises. The subject is theoretical provisions, methodological approaches, methods for determining the strength of the brand on its main features and the formation of management strategies. Methods. Theoretical and practical analysis of works of branding specialists proved the need to use the following methods of research: monographic, analysis and synthesis, structural-logical method, system approach, theoretical generalization, expert methods, correlation-regression analysis. The results are as follows: the differences between the strength and value of the brand, generalized understanding of realistic and emotional components of the brand, offered indicators of their measurement - on a realistic basis by a three-factor model of transformation of brand strength into additional financial flows, emotionally - based on the developed questionnaire, that is, using expert methods, proposed a matrix of brand strength on these features and positioned brand management strategies in accordance with the essence and meaningful load. The main results of the research are proposals for assessing the strength of the brand on the basis of objective and subjective characteristics and their use to build a matrix of positioning strategies for brand management. As the main strategies of brand management it is offered to use the following: strategy of donation, and stratification of the general brand, strategy-aspiration to leadership at use of the strong points and opportunities, exclusive advantages, combining them with own possibilities, strategy of maximization of dominance in the market strengthening the basic direction of innovation, niche strategy - financing specific innovation proposals for target segments of the consumer market, strategy of flank attack to increase cash flows, market exit strategy, strategy of careful promotion, flank donation, donor strategy, attention is paid to the needs of the target audience of consumers in the market for products. The existence of a correlation between the rationalist and emotional characteristics of the brand is proved. Conclusions: brand strength and strategy should be formed on the basis of both realistic and emotional features.